The effect of Ezetimibe and Simvastatin Combination Therapy on percutaneous coronary intervention patients. (1st September 2017) - Lin, Hong; Zhang, Yuan-ming
Abstract: Aims: Evaluating the short-term influence of Ezetimibe and Simvastatin Combination Therapy on LDL-C, TG and hs-CRP expression level in patients with percutaneous coronary intervention. Methods: 57 cases of percutaneous coronary intervention patients were selected, and randomly divided into two groups: Simvastatin (40 mg/day) and Ezetimibe (10 mg/day) combination therapy group (observation group) with 28 patients, Simvastatin (40 mg/day) group (control group) with 29 patients. Each group was treated for 10 days. After treatment, compare blood lipid LDL-C, TG, hs-CRP levels with each other and the results before treatment. Results: Comparison of the results of the 10th day with the baseline: LDL-C, TG decreased significantly (P < 0.01) in the observation group, while the control group did not have a significantly change (P > 0.05). Comparison of observation group and control group: after treatment, LDL-C and TG decreased more significantly in the observation group than the control group (− 27.2% vs − 14.6%, P < 0.05). Whether according to LDL-C < 2.07 mmol/L standard or LDL-C < 1.8 mmol/L standard, the compliance rate of the observation group was significantly better than the control group, the results were (69% vs 28.9%, P < 0.05) and (47.6% vs 13.2% P < 0.05), respectively. After 10 days treatment, comparing to baseline, hs-CRP was significantly lowered in these two groups (P < 0.01). And there is no liver and kidney toxicity, myopathy and other adverse reactions during treatment. Conclusions: Combination therapy of Ezetimibe (10 mg/day) and Simvastatin (40 mg/day) was more effective than mono-therapy with Simvastatin (40 mg/day) on reducing LDL-C, TG and hs-CRP level in percutaneous coronary intervention patients, leading to more significant anti-inflammatory effect.